Avoidance of Medicine Wastage in Private Clinics In Hong Kong: Practitioners’ Perspectives - Simon Yuen; Calvin Cheng; Helen Wong (Asia Pacific Journal of Health Management, 2024)
Hong Kong with its well-established healthcare and medicine system and professional health services is one of the renowned healthiest places in the world. In fact, Hong Kong's healthcare system is running on a dual-track basis comprising public and private sectors. This study intends to explore medicine waste management and sustainability. First, we examine the existing phenomenon of Hong Kong medicine waste. Also, we discuss the causes of medical waste from a private clinic doctors' perspective. In addition, we identifies possible policies and recommendations to minimize the medicine wastage in private clinic in Hong Kong as well as improve the healthcare supply chain practices.